Development through dismemberment of the weak: threat of Polavaram project - Reddy, N. Subba (2006)
The Kalinga Nagar incident at Orissa is a warning to all projects such as the proposed Polavaram project in Andhra Pradesh that will displace about 1,20,000 people. The article critically analyses different projects in AP, with a special emphasis on Polavaram, for which the state government has not declared any resettlement and rehabilitation policy. - Reproduced.
Keywords: Resettlement - India - Orissa; Resettlement - India - Orissa; Resettlement